Speaking Skill Assessment Techniques in Learning English Language - soleh, achmad fathorrosi; Karimullah, Imam Wahyudi; hastuti, nilna widia (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to describe (1) the forms of speaking skills assessment and (2) teachers' solutions in overcoming the obstacles of speaking skills assessment in English learning at LPBA Nurul Jadid. This research used a descriptive qualitative design. The subject of this research is English. This research's objective is to assess speaking skills in Indonesian language learning. The data collection methods used were observation, interview, and documentation. The results of this study show that the technique of assessing speaking skills in English learning uses the form of tests and non-tests, discussion tests in debate learning, and retelling tests in short story learning. Non-test uses observation and portfolio. The aspects assessed are linguistic and non-language aspects. Linguistic aspects include memorization, intonation, structure, and vocals. Non-language aspects are attitude, fluency, expression, and topic mastery. There are three obstacles experienced by teachers in the assessment of speaking skills, namely (1) difficulty in preparing students to face speaking skills learning and (2) difficulty in managing time. There are three solutions offered by teachers in overcoming the obstacles of speaking skill assessment, namely (1) repeating the material, (2) making systematic assessment planning, and (3) conveying the speaking test system or procedure.